Comparative technical and economic analysis of a local sheep breed in Greece and North Macedonia - Skordos D.; Ragkos A.; Papatpukaki C.; Theodoridis A. (Pastoralism and sustainable development: proceedings, 2021)
The development of the sheep sector resulted in the transition from traditional extensive systems to intensive, where local breeds have been gradually replaced by imported improved ones or extensive crossbreeding has taken place. This has been the case in Greece as well as North Macedonia, where cross-breeding between local breeds has also been extensive. This study examines the economic performance of the production systems of the local “Pelagonia” sheep breed - which can be found in the cross-border area of the two countries but is actually witnessing declining populations. The results of a descriptive technical and economic analysis demonstrated that the extensive Pelagonia production systems are more profitable than the intensive - despite lower milk yields– mainly due to significant savings in feeding costs. In addition, it showed that the economic results of the Greek extensive group were better than those of the average Pelagonia farm in North Macedonia. However, a different outcome is yielded when subsidies are not taken into account, as the economic results of the average Pelagonia farm in North Macedonia were more satisfactory than those of the Greek extensive group, indicating that the Greek Pelagonia farms highly rely on income support. The results of the technical and economic analysis are an essential step toward the definition of the framework within which Pelagonia sheep farms will be incorporated towards the emergence of sustainable production systems in both countries.
International e-Workshop organized in the framework of PACTORES project, 2021/07/14-15, Valenzano, Bari, (Italy)